Problematika Linieritas dan Pemenuhan Kualifikasi Akademik Guru dalam Lembaga PAUD - Milla Diah Putri Nazidah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
PAUD’s teachers are the second basic laying figures of education after parents. PAUD’s teachers must have expertise in this field. But in reality there are still many teachers who have not met national standards. The purpose of this research is to discuss the problems of teachers in PAUD’s institutions which include academic qualifications and linearity of graduates. This research uses qualitative method of descriptive approach, techniques used is observation, interview, and documentation, data analysis is done from data collection to conclusion. The results showed that the teachers at RA Bakti 7 Wonorejo did not meet the national standards as PAUD’s teachers, it is known from the graduates of every teacher that nothing is relevant to the field of PAUD. There are 4 teachers with 2 S1 public education and 2 S1 Islamic education. The problem is the lack of human resources of PAUD’s teachers in accordance with national standards.